Modern South Asia : history, culture, political economy - Bose, Sugata, 1956-; Jalal, Ayesha (Routledge, 2023)
"The fifth edition of Modern South Asia draws on the newest historical research and scholarship in the field to interpret and debate key developments in modern South Asian history and historical writing, covering the diverse spectrum of the subcontinent's social, economic and political past. Jointly authored by two leading Indian and Pakistani historians, this definitive study offers a rare depth of historical understanding of the politics, cultures and economies that have shaped the lives of more than a fifth of humanity. This new edition on the 75th anniversary of independence and partition brings the narrative up to the present day, discussing recent events and addressing new themes such as the capture of state power in India by the forces of religious majoritarianism, economic development in the context of the 'rise' of Asia and strategic shifts occasioned by the US withdrawal from Afghanistan and China's increasing role in the region. Providing fresh insights into the structure and ideology of the British raj, the meaning of subaltern resistance, the refashioning of social relations along lines of caste, class, religion and gender, the different strands of anti-colonial nationalism and the dynamics of decolonization, this is an essential resource for all students of the modern history of South Asia in an Indian Ocean and global context"--